سوانح عمری حضرت محمد صاحب بانی اسلام از شردھے پرکاش دیو کا منہج و اسلوب:ایک تجزیاتی مطالعہ: Methodology and Style of ’Biography of Hazrat Muhammad Sahib, Founder of Islam’ by Shradhe Parkash Dev: An Analytical Study - Nazar, Javeria; Safdar, Dr. Sumera (Al-Amīr Research Journal for Islamic Studies, 2024)
The life of the Holy Prophet Muhammad ﷺ has been a subject of continuous study and admiration since the advent of Islam. Both Muslim and non-Muslim biographers have written extensively about him, recognizing his unparalleled significance. Among the non-Muslim contributors, authors from the Indian subcontinent, particularly Hindu writers, have shown respect and devotion in their works. A notable example is Shradhe Parkash Dev’s Biography of Hazrat Muhammad Sahib, Founder of Islam (1907), which provides a balanced and insightful account of the Prophet’s life. Dev’s vivid narrative covers pre-Islamic Arabia and the Prophet’s ancestry, offering an engaging discussion of his life while refuting common misconceptions. The use of both Hindi and Urdu languages enhances the uniqueness of the work, marking it as a significant contribution to early 20th-century biographical literature. Keywords: Holy Prophet ﷺ, Shradhe Parkash Dev, Muslim and non-Muslim biographers, biography, early 20th-century.